Mapping a research-advocacy-policy agenda on human rights and albinism: a mixed methods project - Sheryl Reimer-Kirkham; Barbara Astle; Ikponwosa Ero; Lori Beaman; Bonny Ibhawoh; Elvis Imafidon; Richard Sawatzky; Wisdom Tettey; Meghann Buyco; Emma Strobell (BMC, 2024)
Abstract Background Persons with albinism face challenges to their wellbeing, safety, and security, ranging from vision impairment and skin cancer to stigma and discrimination. In some regions, they also face human rights atrocities including mutilation and murder. Research on human rights and albinism is a relatively new field that has gained momentum since the United Nations appointment of an Independent Expert on the enjoyment of human rights by persons with albinism. In this paper, we present the results of a mixed methods study undertaken to identify priorities for research, advocacy, and policy on albinism and human rights. Methods The first component was a synthesis of peer-reviewed and grey literatures at the nexus of albinism, spiritual/cultural beliefs and practices, and human rights. We then conducted a priority-setting survey, informed by Delphi methods, on extant knowledge-practice gaps and research, advocacy, and policy priorities. Inclusion criteria included demonstrated expertise in the field (e.g., peer-reviewed publications, funded research), membership on national or international associations, or advocacy (civil society organizations) of more than 2 years in albinism and human rights. Thereafter, we gathered leading researchers, policy-makers, and civil society stakeholders for a Roundtable to gain consensus on these priorities. Results Access to skin and vision care, and education were not deemed high priority for research, likely because the evidence supporting the need for these is well established. However, they were priorities for advocacy and policy: what is needed is mobilization of this evidence through advocacy and implementation of such services (policy). Other social determinants of health (rurality, poverty, and gender equality) are present as subtext in the findings, more so than priorities for research, advocacy, or policy, despite their preponderance in the lives of persons with albinism. Research was prioritized on stigma and discrimination; advocacy; and witchcraft, but with some differentiation between Global North and Global South priorities. Priorities for research, advocacy, and policy vary in keeping with the explanatory frameworks at play, including how harmful practices and witchcraft are viewed. Conclusions The lived experience of albinism is profoundly shaped by the social determinants of health (SDOH). Threats to the security and well-being of persons with albinism should be viewed through a human rights lens that encompasses the explanatory frameworks at play.